MENENTUKAN TINGKAT KEPUASAN PELANGGAN PDAM PAYAKUMBUH SETELAH PEMBANGUNAN WATER TREATMENT PLANT BATANG AGAM - Sakri, Harfa; Junaidi, Junaidi; Istijono, Bambang (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2020)
The aim of this research was to measure the level of customer satisfaction with the services of Payakumbuh PDAM after the construction of the Batang Agam Water Treatment Plant as one source of raw water. The result of this research explain that service of Payakumbuh PDAM after construction of Batang Agam Water Treatment Plant which analyzed using the Importance Performance Analysis method. There are 7 question attributes that become measurement points. In the first and second questions attribute about the smooth running of water at the peak hours of morning and evening whose value was in quadrant A where Payakumbuh PDAM should make an effort to improve customer satisfaction which means that these quality attributes need to be improved and improved continuously so that the quality attribute performance regarding smoothness at the peak hours in this quadrant increases and customer satisfaction can be achieved. Besides that, the attributes about water clarity, colorless water, tastes fresh, odorless water and normal temperature have reached quadrant B or known achievement priority. This position shows the quality of raw water product from Batang Agam Water Treatment Plant has been successfully carried out by Payakumbuh PDAM, so that, it must be maintained.